2009
DOI: 10.1002/maco.200905382
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and SEM studies of a new implant bioalloy in physiological electrolytes

Abstract: A new implant Ti-7Al-3V-2Mo-2Fe alloy was elaborated and its behaviour in Ringer-Brown and Ringer solutions (of different pH values) was studied using cyclic potentiodynamic and linear polarisation, electrochemical impedance spectroscopy (EIS) and scanning electron microscopy (SEM) with its link energy dispersive X-ray system (EDX). Cyclic potentiodynamic polarisation curves revealed that the Ti-7Al-3V-2Mo-2Fe alloy is self-passivated in Ringer solutions. Pitting corrosion appeared in alkaline Ringer solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…29,[32][33][34] Also, all E oc values of ternary Ti-6Al-4V alloy have more electronegative values than of quaternary Ti-6Al-4V-1Zr alloy, pointing out a more stable passive state for the new alloy, due to the passive ZrO 2 oxide 10,22 that is presented in the passive layer.…”
Section: Improvement Of Corrosion Resistance From In Time Variations mentioning
confidence: 92%
“…29,[32][33][34] Also, all E oc values of ternary Ti-6Al-4V alloy have more electronegative values than of quaternary Ti-6Al-4V-1Zr alloy, pointing out a more stable passive state for the new alloy, due to the passive ZrO 2 oxide 10,22 that is presented in the passive layer.…”
Section: Improvement Of Corrosion Resistance From In Time Variations mentioning
confidence: 92%
“…From Table 3 can be observed that, in 0.1 M Na 2 SO 4 solution, the new Ti-6Al-2Nb-1Ta alloy presented very low values of the corrosion current densities and rates, placed in the 'perfectly stable' class. Polarisation resistances increased in time showing higher resistances of the passive film and better protective capacities [24][25][26].…”
Section: Corrosion Resistance Resulting From Tafel Diagramsmentioning
confidence: 99%
“…Therefore, the alloy is in the passive state with a (Table 1). Also, the differences jE corr ÀE p j had very low values, showing a very good and very easy tendency to passivation (Table 1) in 0.1 M Na 2 SO 4 solution [24][25][26]. The corrosion potentials shifted to electropositive direction with increasing time.…”
Section: Corrosion Behaviour In 01 M Na 2 So 4 Solutionmentioning
confidence: 99%
“…3) showed a selfpassivation behaviour without active-passive transition potential range but with very large passive potential range, DE p (more 4000 mV, maximum potential limit in our experiments), that represents a very stable protective film [10,[38][39][40]. Corrosion potentials, E corr (Table 1) shifted to more electropositive values for anodised alloy, due to the formation of the thicker, more stable nanolayer on the surface during the anodisation process; also, the increase of E corr suggests that the electrodeposited film acts as a barrier against the corrosion attack [38][39][40]. Passive current densities, i p remained almost constantly on the whole passive potential range, consequently, the existing film progressively thickened; anodised alloy had lower i p values as result of the existence of the anodised nanolayer that moreover strengthened and thickened the native passive film, conferring it higher resistance, and protection [26].…”
Section: Electrochemical Stability Of Anodised Alloymentioning
confidence: 99%
“…4) revealed large arcs, capacitive loops with bigger diameters for anodised alloy that implies higher resistances compared with those of the bare alloy. The impedance values are higher for the anodised alloy proving that the anodised film increased the insulating, protective properties of the alloy native passive film [17,26,[38][39][40][41][42][43].…”
Section: Electrochemical Stability Of Anodised Alloymentioning
confidence: 99%